Pengaruh Iklan Humor pada Kesadaran Merek Milenial di Jakarta (Studi pada Iklan Sampo Head & Shoulders versi Bloopers Joe Taslim) - Volin Stevani Putri; Diah Ayu Candraningrum (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Head and Shoulders is an anti-dandruff shampoo brand owned by the parent company Procter & Gamble (P&G). Head and Shoulders made an interesting advertisement entitled